Deconstructive Reading on Traditional Narratives in English Course Book - Setiawan, Rahmat; Agustina, Eliasanti (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2024)
This research aims to explore deconstructive reading on traditional narratives in coursebook and how the EFL pre-service teachers’ insights on it. This research imposes its theoretical framework in the concepts of Deconstruction, EFL Pre-service Teachers, Literature, Traditional Narrative Text, and Coursebook. The type of this research is qualitative, the approach is case study. The data in this research are text fragmentations from the narrative texts and the statements of the EFL students. The first source of the data is the narrative texts in the coursebook. The second source of the data is interview with some EFL pre-service teachers from various university in Surabaya. The techniques of data collection in this research are documentation and non-structured interview. The technique of data analysis in this research is thematic analysis. The result of the analysis is narrative texts provided by Kemendikbud in English coursebook seem to be conventional and it requires EFL teachers with good sense of literature to help out students to make the meaning relevant with the life they live today. Some interviewed EFL pre-service teachers put some insights that meaning in the traditional narrative texts in the English coursebook. For them, traditional narrative is important, but the interpretative meaning should be deconstructed in more various meaning, not in one-sided claim which one is true and false.